Tourist Perceptions of Majapahit Museum as Character Education Facilities - Stiawan, Ade Denis; Sugiyanto, Sugiyanto; Puji, Rully Putri Nirmala; Soepeno, Bambang; Prasetyo, Guruh; Triyanto, Jefri Rieski (JURNAL HISTORICA, 2022)
Majapahit museum is a museum that has many collections objects and has a variety of character values contained in the object of the collection which he has. The problem in this research is: (1) How is the value of educational objects in the Museum? ; (2) How are tourists’ perception of the Museum Majapahit as a means of Character education?. This study is a study of tourists perception regarding the collection of Majapahit Museum as a means of character education, especially in the value of religious character, tolerance, national enthusiasm, and homeland love. The research method used is qualitative research method with data collection in the form of observations, interviews, and documentation. The results of this study include the perception of tourists after visiting the Museum have a strong character perception of strong character, especially in the value of religious character, tolerance, national enthusiasm, and homeland love. The character grades in the museum's collection objects are also supported by the chairman of Majapahit Museum itself.